Impressionist portraits of mitotic exit: APC/C, K11-linked ubiquitin chains and Cezanne - Bonacci, Thomas (Cell Cycle, 2019)
The Anaphase-Promoting Complex/Cyclosome (APC/C) is an E3 ubiquitin ligase and a key regulator of cell cycle progression. By triggering the degradation of mitotic cyclins, APC/C controls cell cycle-dependent oscillations in cyclin-dependent kinase (CDK) activity. Thus, the dynamic activities of both APC/C and CDK sit at the core of the cell cycle oscillator. The APC/C controls a large number of substrates and is regulated through multiple mechanisms, including cofactor-dependent activation. These cofactors, Cdc20 and Cdh1, recognize substrates, while the specific E2 enzymes UBE2C/UbcH10 and UBE2S cooperate with APC/C to build K11-linked ubiquitin chains on substrates to target them for proteasomal degradation. However, whether deubiquitinating enzymes (DUBs) can antagonize APC/C substrate ubiquitination during mitosis has remained largely unknown. We recently demonstrated that Cezanne/OTUD7B is a cell cycle-regulated DUB that opposes the ubiquitination of APC/C substrates. Cezanne binds APC/C substrates, reverses their ubiquitination and protects them from degradation. Accordingly, Cezanne depletion accelerates APC/C substrate degradation, leading to errors in mitotic progression and formation of micronuclei. Moreover, Cezanne is significantly amplified and overexpressed in breast cancers. This suggests a potential role for APC/C antagonism in the pathogenesis of disease. APC/C contributes to chromosome segregation fidelity in mitosis raising the possibility that copy-number and expression changes in Cezanne observed in cancer contribute to the etiology of disease. Collectively, these observations identify a new player in cell cycle progression, define mechanisms of tempered APC/C substrate destruction and highlight the importance of this regulation in maintaining chromosome stability.